Clinical Implications of Bronchodilator Testing: Diagnosing and Differentiating COPD and Asthma-COPD Overlap. - Annangi, Srinadh; Coz-Yataco, Angel O. (Respiratory Care, 2022)
BACKGROUND: Bronchodilation testing is an important component of spirometry testing, and omitting this procedure has potential clinical implications toward diagnosing respiratory diseases. We aimed to estimate the impact of bronchodilator testing in accurately diagnosing COPD and differentiating COPD from asthma-COPD overlap (ACO). METHODS: The National Health and Nutrition Examination Survey data were analyzed from 2007-2012. Airflow limitation was defined by FEV1/FVC < 0.7. Subjects with pre-bronchodilator airflow limitation were classified into pre-but-not-post-bronchodilator airflow limitation and post-bronchodilator airflow limitation groups. Spirometry-confirmed COPD was defined by persistent airflow limitation on post-bronchodilator spirometry. The American Thoracic Society (ATS) and the Spanish Society of Pneumology and Thoracic Surgery (SEPAR) definitions were used to identify possible ACO subjects. RESULTS: We identified 11,763 subjects ≥ 40 y of age eligible for spirometry; 625 of them had a pre-bronchodilator FEV1/FVC < 0.7 and completed post-bronchodilator spirometry that met ATS spirometry quality standards. A total of 244 (39%) of these subjects had only pre-not-post-bronchodilator airflow limitation, thereby not meeting the definition of spirometrically confirmed COPD. The prevalence of ACO was 7.6% using the modified ATS definition and 19.8% using the modified SEPAR criteria. When bronchodilator testing-based criteria were excluded from ATS and SEPAR definitions, the number of ACO subjects decreased by 39.3% and 12.3%, respectively. CONCLUSIONS: Spirometry with bronchodilation is an important element in the accurate diagnosis of ACO and COPD. Spirometry performed without bronchodilator testing may lead to an estimated misclassification of ACO by 7.6% to 19.8% and overdiagnosis of COPD by 39%.